Poisonous Plants and Related Toxins 2003
DOI: 10.1079/9780851996141.0084
|View full text |Cite
|
Sign up to set email alerts
|

Calcinosis in ruminants due to plant poisoning: contributions on the pathogenesis.

Abstract: The effects of plant-induced hypervitaminosis D on cell differentiation in the skin, aorta and lung of ruminants were studied. Skin and aorta tissue samples from experimentally Solanum glaucophyllum (Sg)-intoxicated cows were obtained and analysed. Also, aortas and lungs of sheep with spontaneous enzootic calcinosis (EC) induced by Nierembergia veitchii (Nv), and the same organs of rabbits intoxicated with Sg, were analysed by electron microscopy and immunohistochemical techniques. Sg-poisoned heifers showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…⁄ = p < 0.01. Gimeno et al, 2004;Razzaque and Lanske, 2006;Fontana and Zanuzzi, 2007;Medici et al, 2008;Zanuzzi et al, 2008;Fontana et al, 2009;Fontana, 2010;Zanuzzi et al, 2010). Morphological modifications have been reported in the crypts of the small intestine of rats treated with metrotrexate (Verburg et al, 2000), and in the mucosa and lamina propria of young rats fed with low protein content diet (Rodrigues et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…⁄ = p < 0.01. Gimeno et al, 2004;Razzaque and Lanske, 2006;Fontana and Zanuzzi, 2007;Medici et al, 2008;Zanuzzi et al, 2008;Fontana et al, 2009;Fontana, 2010;Zanuzzi et al, 2010). Morphological modifications have been reported in the crypts of the small intestine of rats treated with metrotrexate (Verburg et al, 2000), and in the mucosa and lamina propria of young rats fed with low protein content diet (Rodrigues et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Rabbits are useful as experimental model. They are highly susceptible to experimental treatment with S. glaucophyllum in a way similar to the natural intoxication that occurs in ruminants (Dallorso et al, 2001;Gimeno et al, 2004;Fontana and Zanuzzi, 2007;Zanuzzi et al, 2008;2010).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…bone disease, psoriasis, and cancer (Clemens et al 1983, Rice et al 1992, Walters 1992, Bikle & Pillai 1993. Changes in cell differentiation induced by calcinogenic plants have been analysed in skin, aorta and lung , 2004, Portiansky et al 2002.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…The influence of UV light (6 h radiation with 254 nm) in the calcinogenic activity of T. flavescens and N. veitchii has been tested [169]. Mello and Habermehl [170] Cell differentiation damage induced by calcinogenic plants has been analyzed in skin, aorta and lungs [171]. Aguirre et al [172] reported the bone and growth cartilage changes after subacute poisoning of rabbits with S. glaucophyllum.…”
Section: Figure 24mentioning
confidence: 99%